38 The development of a three-dimensional culture system for in vitro studies of the atheroma. (17th November 2015) - Noonan, J; Grassia, G; McInnes, IB; Graham, D; Garside, P; Maffia, P
Abstract : Atherosclerosis is a complex inflammatory disease characterised by endothelial cell (EC) dysfunction, infiltration of macrophages into the vessel wall, and the formation of an atheroma. The surface of the atherosclerotic plaque is covered by a protective "fibrous cap" composed of ECs and smooth muscle cells (SMCs), with the interaction between ECs, SMCs and macrophages being crucial for plaque stability. We have now developed an in vitro model combining these key cell types in a three-dimensional co-culture system representative of the atheroma. Human coronary artery SMCs (CASMCs) were seeded on the underside of a 3 μm pored geltrex coated transwell insert, allowed to attach, and incubated in 6 well plates at 37C/5% CO2 until confluent. Human coronary artery endothelial cells (HCAECs) were then seeded on the upper surface of the transwell membrane and cultured until confluent. Transwell inserts were then transferred to 6 well plates containing phorbol myristate acetate (PMA)-differentiated THP-1 macrophage-like cells. Immunohistochemical analysis of this model identified a confluent monolayer of ECs, a multilayer of SMCs segregated by the transwell insert membrane, and a population of macrophages. Isolation of these distinct cellular layers is a simple method for subsequent investigation by many techniques, including Flow Cytometry and Western Blot. The model described allows for the simultaneous analysis of multiple key cell types involved in atherosclerosis development, providing a useful research tool to be employed to monitor intercellular communication, cell migration dynamics, and stimulation. Supported by the Engineering and Physical Sciences Research Council (EPSRC) grant EP/L014165/1.